The chemistry of iron, cobalt and nickel - Nicholls, David, 1935- (Pergamon texts in inorganic chemistry ;, 1973)
The Chemistry of Iron, Cobalt and Nickel deals with the chemistry of iron, cobalt, and nickel and covers topics ranging from the occurrence and distribution of all three elements to their properties, allotropy, and analytical chemistry. Compounds of iron, cobalt, and nickel in both low and high oxidation states are also discussed. This book is divided into three sections and begins with the history of iron, along with its occurrence and distribution, allotropy, and preparation and industrial production. The nuclear, physical, and chemical properties of iron, as well as the biological importanc.